MEDIAÇÃO JUDICIAL NA COMARCA DE IJUÍ - Campos, Iris F. A.; Schonardie, Elisiane; Correa, Guilherme M.; Gaspary, Maria L. P.; Hatem, Nasser; Souza, Tania M. d.; Sand, Adriana P. V. D.; Avila, Patricia M. d.; Avila, Cassiana A. (Salão do Conhecimento, 2013)
Resumo